Genetic Evidence That Chain Length and Branch Point Distributions Are Linked Determinants of Starch Granule Formation in Arabidopsis . Issue 4 (25th June 2014) - Pfister, Barbara; Lu, Kuan-Jen; Eicke, Simona; Feil, Regina; Lunn, John E.; Streb, Sebastian; Zeeman, Samuel C.
Abstract : Glucose polymers with both the right branching pattern and the right chain length distribution are required to produce semicrystalline starch granules. Abstract: The major component of starch is the branched glucan amylopectin. Structural features of amylopectin, such as the branching pattern and the chain length distribution, are thought to be key factors that enable it to form semicrystalline starch granules. We varied both structural parameters by creating Arabidopsis ( Arabidopsis thaliana ) mutants lacking combinations of starch synthases (SS s) SS1, SS2, and SS3 (to vary chain lengths) and the debranching enzyme ISOAMYLASE1-ISOAMYLASE2 (ISA; to alter branching pattern). The isa mutant accumulates primarily phytoglycogen in leaf mesophyll cells, with only small amounts of starch in other cell types (epidermis and bundle sheath cells). This balance can be significantly shifted by mutating different SS s. Mutation of SS1 promoted starch synthesis, restoring granules in mesophyll cell plastids. Mutation of SS2 decreased starch synthesis, abolishing granules in epidermal and bundle sheath cells. Thus, the types of SS s present affect the crystallinity and thus the solubility of the glucans made, compensating for or compounding the effects of an aberrant branching pattern. Interestingly, ss2 mutant plants contained small amounts of phytoglycogen in addition to aberrant starch. Likewise, ss2ss3 plants contained phytoglycogen, but were almost devoid of glucan despite retaining other SS isoforms. Surprisingly, glucan production was restored in the ss2ss3isa triple mutants, indicating that SS activity in ss2ss3 per se is not limiting but that the isoamylase suppresses glucan accumulation. We conclude that loss of only SS s can cause phytoglycogen production. This is readily degraded by isoamylase and other enzymes so it does not accumulate and was previously unnoticed.